Uterine cervical Müllerian adenosarcoma possibly arising from ovarian cystadenofibroma: A case report and review of the literature - Zhu, Xinxin; Peng, Chao; Huang, Yan; Zhou, Yingfang (Frontiers in Oncology, 2023)
Uterine cervical Müllerian adenosarcoma (MA), a rare malignant tumor of the female reproductive organs, is composed of a benign epithelium and a low-grade malignant stromal component. Because few studies have investigated the clinical management of MA, misdiagnosis often occur. Therefore, we proposed an optimal course of clinical management for patients with MA. MA is possibly a malignant transformation of the cystadenofibroma. In this study, we present a case of a 46-year-old woman who presented with symptoms of MA of the uterine cervix, such as metrorrhagia and a cyst in the cervical canals, after transvaginal excision of the left ovarian mucinous cystadenofibroma.